2011
DOI: 10.1063/1.3666818
|View full text |Cite
|
Sign up to set email alerts
|

Planar jumping-drop thermal diodes

Abstract: Phase-change thermal diodes rectify heat transport much more effectively than solid-state ones, but are limited by either the gravitational orientation or one-dimensional configuration. Here, we report a planar phase-change diode scalable to large areas with an orientation-independent diodicity of over 100, in which water/vapor is enclosed by parallel superhydrophobic and superhydrophilic plates. The thermal rectification is enabled by spontaneously jumping dropwise condensate which only occurs when the superh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
193
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(199 citation statements)
references
References 13 publications
0
193
0
Order By: Relevance
“…30,99 In addition, the interfacial resistances, i.e., thermal grease, between the sample substrate and test rig have led to a lack of repeatability in heat transfer measurements. Recently, a few studies have conducted experimental investigations in pure vapor environments (no NCGs) 47,93,100,101 . The first performance measurement was achieved by Boreyko et al 100 To specifically quantify condensation heat transfer performance, Miljkovic et al 47 tested superhydrophobic nanostructured CuO surfaces over a range of supersaturations (1.02 < S < 1.6) (Figure 7c).…”
Section: Heat Transfer Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…30,99 In addition, the interfacial resistances, i.e., thermal grease, between the sample substrate and test rig have led to a lack of repeatability in heat transfer measurements. Recently, a few studies have conducted experimental investigations in pure vapor environments (no NCGs) 47,93,100,101 . The first performance measurement was achieved by Boreyko et al 100 To specifically quantify condensation heat transfer performance, Miljkovic et al 47 tested superhydrophobic nanostructured CuO surfaces over a range of supersaturations (1.02 < S < 1.6) (Figure 7c).…”
Section: Heat Transfer Experimentsmentioning
confidence: 99%
“…Recently, a few studies have conducted experimental investigations in pure vapor environments (no NCGs) 47,93,100,101 . The first performance measurement was achieved by Boreyko et al 100 To specifically quantify condensation heat transfer performance, Miljkovic et al 47 tested superhydrophobic nanostructured CuO surfaces over a range of supersaturations (1.02 < S < 1.6) (Figure 7c). They demonstrated that in the jumping regime where S < 1.12, heat transfer coefficients were h jumping ≈ 92 kW/m 2 K, 30% higher than that of state-of-the-art dropwise condensing copper surfaces.…”
Section: Heat Transfer Experimentsmentioning
confidence: 99%
“…One of the main technological challenges is to create such a surface, so as to allow condensation and evacuation of the droplets to take place in a continuous manner. Droplet coalescence is a complex physical phenomenon and optimisation of kinematic conditions leading to surface dewetting and jumping of droplets is of paramount importance for processes like heat transfer, de-icing, atmospheric water harvesting or dehumidification [4][5][6]. Dropwise condensation heat transfer performance can be enhanced by allowing condensed droplets to be removed rapidly from the surface to minimize the thermal barrier [7].…”
Section: Introductionmentioning
confidence: 99%
“…Dropwise condensation heat transfer performance can be enhanced by allowing condensed droplets to be removed rapidly from the surface to minimize the thermal barrier [7]. Recently, researchers showed that superhydrophobic surfaces provide a higher mobility of condensates, which may enhance the heat transfer performance [1][2][3][4][5][6][7]. Coalescence-induced jumping phenomena occur on superhydrophobic surfaces but within a small range of initial droplet radii.…”
Section: Introductionmentioning
confidence: 99%
“…3 These phenomena have sparked an interest in spontaneous drop detachment and lift-off, with several authors reporting similar observations on artificial substrates. The drop recoil-and-jump mechanism has been successfully exploited for enhanced heat exchange, [4][5][6][7][8] as the spontaneous jump of coalescing droplets provides an efficient way to remove liquid from a cooler surface. The same physical mechanism has been applied in single-droplet, non-coalescence based, capillary-to-inertial energy conversion by melting-initiated 9,10 and electrowetting-actuated a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%